PENGARUH MANAJEMEN KONFLIK, MOTIVASI KERJA, DAN KEPUASAN KERJA TERHADAP KIN ERJA KEPALA MADRASAH TSANAWIYAH DI KOTA MEDAN - NASUTION, INOM (JURNAL ILMIAH EDUCATIONAL MANAGEMENT, 2011)
The objective of this research is to find out the effect of conflict management, work motivation and job satisfaction on the performance of principalâs madrasah tsanawiyah. Survey method was applied to this research and data had been analyzed with path analysis by putting all variables in correlation matrix. In this research the madrasah tsanawiyah principals have been chosen as units of analysis and 55 respondents were selected randomly. The results of this research are the performance of madrasah tsanawiyah principal is affected directly by ability of conflict management, work motivation. The job satisfacÂ¬tion has the greatest effects to the madrasah tsanawiyah principalâs. This research concluded that variations of the performance of madrasah tsanawiyah principal could be affected by the variations of conflict management, work motivation and job satisfaction.Keywords: conflict management, work motivation and job satisfaction